1996
DOI: 10.1046/j.1365-2249.1996.d01-759.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA expression in the liver of patients with primary biliary cirrhosis (PBC) and chronic hepatitis B (CHB)

Abstract: SUMMARYThe expression of cytokine mRNA species was determined in liver biopsies from six normal subjects, 18 patients with PBC and 14 patients with hepatitis B e antigen (HBeAg)-positive CHB using a reverse transcriptase-polymerase chain reaction (RT-PCR) technique. cDNA, obtained by reverse transcription using oligo d(T) primers, was amplified by PCR using primers specific for the coding region of seven different cytokines (IL-1, IL-2, IL-4, IL-5, IL-6, interferon-gamma (IFN-°), tumour necrosis factoralpha (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 33 publications
4
42
0
1
Order By: Relevance
“…27 Defects may be present in 1 or more of these pathways in PBC patients that could be the basis of enhanced cytokine synthesis. Furthermore, the monocyte PAMP-induced cytokine production observed in our study appears compatible with previously obtained data [28][29][30][31][32] that implicate a significant role of Th-1 cytokines in the pathogenesis of PBC. We note, however, that Th-2 cytokines, such as IL-5, IL-6, and IL-10, also have been detected in PBC livers, 29,31 indicating that both Th-1 and Th-2 cytokines, possibly during different stages of the disease, might be involved in the pathogenesis of PBC.…”
Section: Discussionsupporting
confidence: 92%
“…27 Defects may be present in 1 or more of these pathways in PBC patients that could be the basis of enhanced cytokine synthesis. Furthermore, the monocyte PAMP-induced cytokine production observed in our study appears compatible with previously obtained data [28][29][30][31][32] that implicate a significant role of Th-1 cytokines in the pathogenesis of PBC. We note, however, that Th-2 cytokines, such as IL-5, IL-6, and IL-10, also have been detected in PBC livers, 29,31 indicating that both Th-1 and Th-2 cytokines, possibly during different stages of the disease, might be involved in the pathogenesis of PBC.…”
Section: Discussionsupporting
confidence: 92%
“…Th1 cells are important for the pathogenesis of various autoimmune diseases, 29 whereas Th2 cells contribute to allergic diseases. 30 According to several previous reports, in the liver of PBC, Th1 was found to be dominant [3][4][5]31 or present in combination with Th2. 32 The cytokines IFN-g and IL-4, IL-6 or IL-10 are hallmarks of Th1 and Th2, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…This technique pinpointed the target sites for specimen collection and allowed us to investigate the gene expression of cytokines and TLRs in each specific liver area. Although several studies have analyzed cytokine expression in liver of PBC patients, [1][2][3][4][5][6][7] this is the first study to measure the steady-state expression levels of cytokines and TLRs in early stages of PBC within separate liver microenvironments of the portal tract and liver parenchyma. Th1 cells are important for the pathogenesis of various autoimmune diseases, 29 whereas Th2 cells contribute to allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although both Th1 and Th2 cells are found in the liver of patients with PBC, 10 assessment of the cytokine profile in the liver of patients with PBC gives conflicting results: Martinez et al 11 found evidence of Th2-type cytokines with increased messenger RNA for IL-5 when compared with livers from patients with autoimmune hepatitis, whereas Harada et al 12 found evidence to support a Th1 profile, with increased messenger RNA for IL-4, although interferon-␥ was seen around damaged portal tracks. Shindo et al 13 were able to detect in the liver of PBC patients messenger RNA for interferon-␥ but not for IL-1, 2, 4, 5, or 6. Dienes et al 14 also found evidence for a Th1 predominance.…”
mentioning
confidence: 97%